2014
DOI: 10.1590/s0100-06832014000600007
|View full text |Cite
|
Sign up to set email alerts
|

Index of soil physical quality of hardsetting soils on the brazilian coast

Abstract: SUMMARYMany soils have a hard-setting behavior, also known as cohesive or "coesos". In such soils, the penetration resistance increases markedly when dry and decreases considerably when moist, creating serious limitations for plant emergence and growth. To evaluate the level of structure degradation in hardsetting soils with different texture classes and to create an index for assessing soil hardness levels in hard-setting soils, six soil representative profiles were selected in the field in various regions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…According to Machado et al (2008), the water retention curve could directly affect the management and practices that should be used in agricultural systems. From the SWRC it is possible to determine the S index, developed by Dexter (2004aDexter ( , 2004bDexter ( , 2004c, that has been utilized as an indicator of the soils physical quality (Rosseti et al, 2013;Lima et al, 2014;Melo Filho et al, 2015). This indicator is based on the inflection point of the SWRC model proposed by van Genuchten (1980), having its values highly correlated with soil density, total porosity, macroporosity, and soil organic matter (Dexter, 2004a;Andrade & Stone, 2008;Silva et al, 2012;Cunha et al, 2011).…”
Section: Agriculturalmentioning
confidence: 99%
“…According to Machado et al (2008), the water retention curve could directly affect the management and practices that should be used in agricultural systems. From the SWRC it is possible to determine the S index, developed by Dexter (2004aDexter ( , 2004bDexter ( , 2004c, that has been utilized as an indicator of the soils physical quality (Rosseti et al, 2013;Lima et al, 2014;Melo Filho et al, 2015). This indicator is based on the inflection point of the SWRC model proposed by van Genuchten (1980), having its values highly correlated with soil density, total porosity, macroporosity, and soil organic matter (Dexter, 2004a;Andrade & Stone, 2008;Silva et al, 2012;Cunha et al, 2011).…”
Section: Agriculturalmentioning
confidence: 99%
“…Anghinoni, Carvalho and Costa (2013) found that the tools currently used to evaluate soil physical quality are insufficient for soils under agricultural processes. According to Lima et al (2014), the S-index can be used as a complementary parameter for the soil morphological description in the field.…”
Section: S-index Ofmentioning
confidence: 99%